Potentials and challenges of a living lab approach in research on mobile participation - Åström Joachim; Ruoppila Sampo; Ertiö Titiana; Karlsson Martin; Thiel Sarah-Kristin (United States, 2022)
This paper discusses potentials and challenges of living lab approach in studying pervasive mobile participation, including reporting experiences of a living lab experiment currently conducted in Turku, Finland. It shows that the living lab approach offers both new opportunities and challenges when implemented in the urban governance context. In general, living labs hold great potential for researching participatory processes enabled by state-of-the-art technology in real world contexts. However, conducting experiments in those real life contexts presents a number of inherent difficulties that makes the potential essentially vulnerable, such as usability issues and political ambivalence on change.
Adjunct Proceedings of the 2015 ACM International Joint Conference on Pervasive and Ubiquitous Computing and Proceedings of the 2015 ACM International Symposium on Wearable Computers